Effectiveness of a guided online mindfulness-focused intervention in a student population: Study protocol for a randomised control trial. Issue 3 (24th March 2020) - Schultchen, Dana; Küchler, Ann-Marie; Schillings, Christine; Weineck, Felicitas; Karabatsiakis, Alexander; Ebert, David D.; Baumeister, Harald; Pollatos, Olga
Abstract : Background: Previous studies show that university students experience higher psychological stress than the general population, resulting in increased vulnerability for mental disorders for the student population. Online mindfulness interventions will be delivered to students as a potentially promising and more flexible approach compared to face-to-face interventions with the aim of improving their mental health. This study purposes to investigate the effectiveness of a guided online mindfulness-focused intervention for university students by using both self-reported and psychobiological measures. Methods and analyses: In this multicentre, two-armed randomised controlled trial with a parallel design, a guided version of the online mindfulness-focused intervention 'StudiCare Mindfulness' will be compared with a waitlist control group. In total, 120 participants will be recruited at different universities (of Applied Sciences) in (Neu-) Ulm. Data will be assessed prior to randomisation, after eight weeks (post-intervention) and six months after randomisation (follow-up). The primary outcome measure is mindfulness. The secondary outcome measures include depression, anxiety and stress levels, well-being, interoceptive sensibility, emotion regulation and alexithymia. Psychobiological parameters comprise interoceptive accuracy, hair cortisol and FKBP5 genotype. Sociodemographic variables, treatment expectations, side and adverse side effects, as well as intervention satisfaction and adherence will be assessed. All data analyses will be conducted according to the intention-to-treat principle. Ethics and dissemination: All study procedures have been approved by the Ethics Committee of Ulm University (application No. 48/18). The findings will be disseminated widely through peer-reviewed publications and conference presentations. Trial registration number: DRKS00014701.